The Role of Judicial accounting in Limiting Creative Accounting Practices in Light of International Accounting Standards (An Exploratory Study in the Iraqi Judiciary) - Hassoon, Forat Sattar; khilkhal, Naeem sabah; AL-Hamzawi, Akram Abbas Rhaif (The journal of contemporary issues in business and government, 2021)
The research aims to address the knowledge bases of both judicial and creative accounting, as well as indicate the role that judicial accountability can play in limiting creative accounting practices in light of international accounting standards. Three hypotheses have been put forward, namely: (1) There is no relationship between the practiced of activities and procedures by creative accounting and judicial accounting practices, (2) The high rates of lawsuits and legal disagreements over financial and marketable matters require the use of judicial accountability, (3) there is no differences among the opinions of external auditors and legal and judicial personnel regarding the role of judicial accountability in limiting creative accounting practices. The research was applied to a sample of the auditors of the Financial Supervision Bureau and workers in the Iraqi law and justice. In order to achieve the objectives of the research and test its hypotheses, a questionnaire was designed and distributed to the members of the sample. A set of appropriate statistical methods was used to analyze the data such as the mean, standard deviation, and mannequin test. The research also reached a set of conclusions, the most important of which was that judicial accountability can help reduce unwanted practices of creative accounting in economic units.